Financial development and income inequality at different levels of institutional quality - Law, Siong Hook; Tan, Hui Boon; Wan Ngah, Wan Azman Saini (M.E. Sharpe, 2014)
We examine whether the relationship between financial development and income inequality varies with levels of institutional quality. The empirical evidence based on the threshold regression approach shows that there indeed exists an institutional quality threshold effect in the relationship between financial development and income inequality. Financial development tends to reduce income inequality only after a certain threshold level of institutional quality has been achieved. Until then, the effect of financial development on income inequality is nonexistent. This finding suggests that institutional quality affects the link between financial development and income inequality, reflecting the notion that better quality finance results in more equal income distribution.